Analisis Kriminologis terhadap Kejahatan Pembunuhan Berencana yang Dilakukan oleh Orang Terdekat: Studi pada Polresta Bandar Lampung - Albertus Agung Hagai Beni Parhualar Sidauruk; Fristia Berdian Tamza; Firganefi Firganefi (Mahkamah : Jurnal Riset Ilmu Hukum, 2024)
Crime is one of the forms of actions that violate social norms in society. One of the criminal offenses frequently occurring in communities is murder. The focus of this study is to explore the factors that trigger premeditated murder by individuals closely related to the victim and to analyze the efforts made by the police in handling such cases. This research employs an empirical approach, also known as a sociological legal study or field analysis. The respondents in this study include the police officials from Polresta Bandar Lampung, criminal investigators from Polresta Bandar Lampung, and criminal law lecturers from the Faculty of Law at Universitas Lampung. Data were collected through literature reviews and field observations, and analyzed qualitatively. The findings indicate several factors contributing to premeditated murder by close associates, including inadequate economic conditions, low education levels, revenge, and drug use. The police address premeditated murder through both penal and non-penal efforts. Penal efforts involve direct handling of cases by conducting investigations, inquiries, and arrests. Meanwhile, non-penal efforts focus on preventive measures aimed at preventing crimes before they occur. The primary focus of non-penal measures is managing the conditions that trigger criminal acts.